Occurrence of antimicrobial serin-proteinases in sunflower seeds - Mendieta, Julieta Renee (2004)
Using an experimental approach directed to the isolation of antimicrobial proteins, we have detected the presence of a trypsin inhibitor (TI) with associated antifungal activity in sunflower seeds. Purification of the isolated protein by affinity chromatography on a trypsin-agarose matrix confirmed that a trypsin inhibitor was responsible for the inhibition of spore germination of the fungal pathogen Sclerotinia sclerotiorum. The protein is a potent antifungal compound as it can completely inhibit the germination of S. sclerotiorum ascospores at a concentration of 14 μg/ml. The putative contribution of this TI to control fungal invasion is discussed.